2021
DOI: 10.2196/29329
|View full text |Cite
|
Sign up to set email alerts
|

Health Belief Model Perspective on the Control of COVID-19 Vaccine Hesitancy and the Promotion of Vaccination in China: Web-Based Cross-sectional Study

Abstract: Background The control of vaccine hesitancy and the promotion of vaccination are key protective measures against COVID-19. Objective This study assesses the prevalence of vaccine hesitancy and the vaccination rate and examines the association between factors of the health belief model (HBM) and vaccination. Methods A convenience sample of 2531 valid participants from 31 provinces and autonomous regions of ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
106
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(122 citation statements)
references
References 68 publications
14
106
2
Order By: Relevance
“…A set of multi-item self-report measures were developed with reference to prior research on vaccination to assess the following psychosocial constructs from relevant models such as the health belief model [35][36][37][38][39][40]59,60], the theory of planned behaviour [45,46,61] and social cognitive theory [45][46][47]: perceived risk of COVID-19 (including items involving perceived susceptibility and severity of COVID-19 infection) (5-items); perceived benefits (6-items); COVID-19 vaccination concerns (5-items); trust (3-items); subjective norm (3-items); moral norm (3-items); necessity of the vaccine (2-items). Items were rated on a 5-point Likert scale ranging from 1 indicating 'Strongly agree' to 5 'Strongly disagree'.…”
Section: Psychosocial Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…A set of multi-item self-report measures were developed with reference to prior research on vaccination to assess the following psychosocial constructs from relevant models such as the health belief model [35][36][37][38][39][40]59,60], the theory of planned behaviour [45,46,61] and social cognitive theory [45][46][47]: perceived risk of COVID-19 (including items involving perceived susceptibility and severity of COVID-19 infection) (5-items); perceived benefits (6-items); COVID-19 vaccination concerns (5-items); trust (3-items); subjective norm (3-items); moral norm (3-items); necessity of the vaccine (2-items). Items were rated on a 5-point Likert scale ranging from 1 indicating 'Strongly agree' to 5 'Strongly disagree'.…”
Section: Psychosocial Factorsmentioning
confidence: 99%
“…Of particular interest are the potentially modifiable psychological determinants of vaccine hesitancy. Studies that applied Social Cognition Models [45][46][47] in context of COVID-19 vaccination indicate that such intentions and behaviours are reasoned processes that are determined by beliefs such as risk perceptions [22,23,26,28,[30][31][32][33]35,39,48], vaccination attitudes (i.e., benefits [22,26,28,29,31,32,[35][36][37][39][40][41]48], concerns [22,23,27,28,30,[32][33][34][35][36][37]39,41,48], necessity [29,30,33]), social norms [30,36,37], moral norms [22,…”
Section: Introductionmentioning
confidence: 99%
“…In this context, previous studies revealed the influence of individual and group differences on vaccine hesitancy such as perceived risk of COVID-19 infection [18,19], confidence in the capacity of health services to respond to the COVID-19 pandemic [20], and trust in authorities [21,22]. Vaccine-specific issues such as confidence in the efficacy of the vaccines [23][24][25][26], fear of side effects [19,25], and high conspiracy beliefs around the vaccines [27] were also revealed to predict COVID-19 vaccine hesitancy.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical models, such as the Health Belief Model, 17 have been used in recent research to help explain attitudes toward the vaccine and vaccine hesitancy for the COVID-19 vaccine during the pandemic. 18. , 19.…”
Section: Introductionmentioning
confidence: 99%
“…, 21. Perceived barriers and benefits have been found to be associated with vaccine hesitancy and vaccination uptake intention, 18 with barriers decreasing one's intention to receive the COVID 19 vaccine and benefits increasing their vaccination uptake intention. 20 With approximately 57% of the U.S. indicating intention to receive the vaccine and greater hesitancy among Latino Americans than non-Hispanic whites, 22 , 23 it is important to understand what may prevent this population from getting vaccinated.…”
Section: Introductionmentioning
confidence: 99%